The Exploration of Social Support and Social Networks in Homeless and Vulnerably-Housed Women - Rattelade, Stephanie Anne (Université d'Ottawa / University of Ottawa, 2016)
Social support is best understood from a gendered perspective. Women place more emphasis on their social relationships than men, relying on them to cope with stressful situations. Women’s social relationships become crucial during experiences of homelessness as they rely on their relationships to address basic needs. This paper explored how social support and social networks are experienced within homelessness and housing vulnerability. Two studies examined social support and social networks in homeless and vulnerably-housed women. Study One used a quantitative approach to examine group differences on social support and social network characteristics. Forty-nine homeless and forty-three vulnerably-housed women completed three measures to assess their social networks, social support networks, and global social support. Results showed similar social networks and global social support scores between groups. However, vulnerably-housed women reported fewer social support network members than homeless women, suggesting they have fewer supportive individuals in their lives. Study two used a qualitative approach to understand how homeless and vulnerably-housed women experience social support. Ten homeless and ten vulnerably-housed women discussed their social networks and social support through semi-structured interviews. Responses were used to develop a model of social support interactions and highlighted new aspects of the experience. Participants described how they used strategies to offer and elicit support with their networks, as well as how their contexts shaped their interactions. The positive and negative outcomes from these interactions also became part of the contexts that influenced future interactions. These findings offer new considerations for social support theory and suggestions for service provision.
Keywords: homelessness; social support; social network; women